Safety and Tolerability of Sodium Thiosulfate in Patients with an Acute Coronary Syndrome Undergoing Coronary Angiography: A Dose-Escalation Safety Pilot Study (SAFE-ACS). (24th September 2020) - de Koning, Marie-Sophie L. Y.; Assa, Solmaz; Maagdenberg, Carlijn G.; van Veldhuisen, Dirk J.; Pasch, Andreas; van Goor, Harry; Lipsic, Erik; van der Harst, Pim
Abstract : Background . In animal studies, hydrogen sulfide (H2 S) has been shown to protect the heart from ischemia-reperfusion injury. This study evaluates the safety and tolerability of the H2 S donor sodium thiosulfate (STS) in patients with acute coronary syndrome (ACS). Methods . Eighteen patients, undergoing coronary angiography for ACS, received STS intravenously immediately after arrival at the catheterization laboratory according to a "3 + 3 dose-escalation design" with fixed dosing endpoint (0, 2.5, 5, 10, 12.5, and 15 grams). This first dose STS was combined with verapamil and nitroglycerin required for transradial procedures. A second dose STS was administered 6 hours later. Primary endpoint was dose-limiting toxicity, defined as significant hemodynamic instability or death up to 24 hours or before discharge from the coronary care unit. Secondary outcomes included the occurrence of anaphylaxis, nausea, vomiting, and systolic blood pressure (SBP) course. Results . Sixteen patients received two dosages of STS and two patients one dosage. None of the patients reached the primary endpoint, nor experienced a serious adverse event. We observed a clinically well-tolerated decline in SBP 1 hour after administration of the first STS dose and concomitant verapamil/nitroglycerin. SBP for all patients together reduced 16.8 (8.1–25.5) mmHg (P = 0.0008 ). No significant decline in SBP occurred after the second dose. Mild nausea was observed in one patient. Conclusion . This is the first report on sodium thiosulfate administration in patients with acute coronary syndromes. Our data suggest that sodium thiosulfate was well tolerated in this setting. The potential benefit of this intervention has to be examined in larger studies.